Consequences of Online Misinformation on COVID-19: Two Potential Pathways and Disparity by eHealth Literacy - Kim, Hye Kyung; Tandoc, Edson C. (Frontiers in Psychology, 2022)
The COVID-19 pandemic poses an unprecedented threat to global human wellbeing, and the proliferation of online misinformation during this critical period amplifies the challenge. This study examines consequences of exposure to online misinformation about COVID-19 preventions. Using a three-wave panel survey involving 1,023 residents in Singapore, the study found that exposure to online misinformation prompts engagement in self-reported misinformed behaviors such as eating more garlic and regularly rinsing nose with saline, while discouraging evidence-based prevention behaviors such as social distancing. This study further identifies information overload and misperception on prevention as important mechanisms that link exposure to online misinformation and these outcomes. The effects of misinformation exposure differ by individuals’ eheath literacy level, suggesting the need for a health literacy education to minimize the counterproductive effects of misinformation online. This study contributes to theory-building in misinformation by addressing potential pathways of and disparity in its possible effects on behavior.